Efektivitas Kepemimpinan Kepala Sekolah Dalam Penerapan Kurikulum Merdeka - Erik Hidayat; Anggiat Pardosi; Irwan Zulkarnaen (Universitas Cokroaminoto Palopo, 2023)
The presence of independent learning is a major transformation in the world of education in Indonesia. The essence of the independent learning curriculum is to create a student-centered learning process. In implementing independent learning, the national education system gives a signal that curriculum development is handed back to the education unit. Based on this, schools as educational units have the freedom to develop the curriculum in accordance with the competencies they have independently. The purpose of this research is to identify the role of the principal in implementing the independent curriculum at SMPN 195 Jakarta. This study uses a qualitative approach. The research is located at SMPN 195 Jakarta. Data collection techniques using interview techniques, documentation and observation. Data sources in this study are divided into primary and secondary data. The primary data in this study are: (1) school principals, (2) educators/educational staff (3) other parties needed to obtain information. Secondary data obtained through; journals, online newspapers, web, books and various literature. Data analysis with stages: data reduction (reduction), data presentation (display), and verification or conclusion (conclusion drawing). Testing the validity of the data includes testing internal validity (credibility), external validity (transferability), reliability (dependability), and objectivity (confirmability). Observation results show that there are still several problems, namely: (1) limited teacher competence in relation to the independent curriculum, (2) implementation of differentiated learning that is not optimal, (3) implementation of the use of IT that is not yet comprehensive in various activities, especially in learning activities. The role of the Head of SMPN 195 Jakarta, as a leader in the education unit in applying independent learning, namely by planning, organizing, implementing, and evaluating.